Congruency effects in dot comparison tasks: Convex hull is more important than dot area. - Camilla Gilmore; Lucy Cragg; Grace Hogan; Matthew Inglis (2016)
Data from the studies reported in Gilmore, C., Cragg, L., Hogan, G., & Inglis, M. (in press). Congruency effects in dot comparison tasks: Convex hull is more important than dot area. Journal of Cognitive Psychology. doi:10.1080/20445911.2016.1221828Experiment 1. This is a by-items dataset with the following variables:ProbNum: Problem numberCHratio: Convex hull ratio of the arraysDotratio: Cumulative dot area ratio of the arraysNumratio: Numerical ratio of the arraysMeanAge: Year group mean ageAccuracy: Mean accuracyExperiment 2. This is a by-items dataset with the following variables:ProbNum: Problem numberCHratio: Convex hull ratio of the arraysDotratio: Cumulative dot area ratio of the arraysNumratio: Numerical ratio of the arraysTiming: Display time in msAccuracy: Mean accuracy